A Model of Forced Saving Based upon Differential Expectations - Hicks, Michael (Quarterly Journal of Economics, 1980)
Journal Article A Model of Forced Saving Based Upon Differential Expectations Get access Michael Hicks Michael Hicks Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 95, Issue 1, August 1980, Pages 181–185, https://doi.org/10.2307/1885355 Published: 01 August 1980